2013
DOI: 10.1137/120876939
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Existence and Robustness of REM/Non-REM Cycling in Physiologically Based Models of REM Sleep Regulatory Networks

Abstract: Typical human sleep throughout the night consists of alternating periods of rapid eye movement (REM) sleep and non-REM (NREM) sleep. This ultradian rhythm of NREM/REM cycling is thought to be produced by the state-dependent activity of "REM-on" and "REM-off" brainstem and hypothalamic neuronal populations that, respectively, promote or suppress REM sleep. Synaptic interactions among these populations define REM sleep regulatory networks; however, the identity of the key neuronal populations in these networks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…6 ). These firing rate modulations mirror the accumulation and dissipation of REM sleep pressure 33 , 34 , and implementation of such slow modulations of REM-off neurons in circuit models can account for the temporal dynamics of REM/NREM alternations 38 , 39 . Previous studies have shown that REM sleep deprivation for several hours decreased/increased the activity of REM-off/REM-on neurons 40 and increased the expression of brain-derived neurotrophic factor in the pons 41 , 42 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…6 ). These firing rate modulations mirror the accumulation and dissipation of REM sleep pressure 33 , 34 , and implementation of such slow modulations of REM-off neurons in circuit models can account for the temporal dynamics of REM/NREM alternations 38 , 39 . Previous studies have shown that REM sleep deprivation for several hours decreased/increased the activity of REM-off/REM-on neurons 40 and increased the expression of brain-derived neurotrophic factor in the pons 41 , 42 .…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent studies have highlighted the importance of GABAergic inhibition between REM-on and REM-off neurons 7 , 9 , 11 , 35 . Although fast GABAergic interactions can account for rapid transitions between brain states, they are insufficient to explain the temporal dynamics of NREM/REM alternation on a timescale of minutes (rodents) to hours (humans); a separate, slow-varying process is required 38 , 39 . Here, in addition to confirming the correlation between the REM episode duration and subsequent inter-REM interval in mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the performances of network models have been explored (Diniz Behn and Booth, 2012;Diniz Behn et al, 2013;Weber, 2017) and these models can replicate sleep dynamics (Diniz-Behn and Booth, 2010) as well as statedependent neural firing (Tamakawa et al, 2006). However, few studies have reported how the strength of synaptic connections between wake-and sleep-promoting populations contribute to the sleep architectures.…”
Section: Implications Of the Current Studymentioning
confidence: 99%
“…Reciprocal excitatoryinhibitory connections (McCarley and Hobson, 1975;Diniz Behn et al, 2007;Diniz-Behn and Booth, 2010;Diniz Behn and Booth, 2012;Booth et al, 2017) and mutual inhibitory interactions (Saper et al, 2001) can be recognized as key network motifs within sleep-wake regulating circuits. Although their dynamics have been explored (Diniz Behn and Booth, 2012;Diniz Behn et al, 2013;Weber, 2017), and those models can replicate sleep architecture of humans and animals (Diniz-Behn and Booth, 2010) as well as state-dependent neural firing (Tamakawa et al, 2006), few studies have investigated how the strength of synaptic connections between wake-and sleep-promoting populations contribute to sleep dynamics. As controlling neural activity at high spatiotemporal resolution in vivo becomes feasible experimentally, computational approaches can be considered as complementary approaches for investigating the role of specific neural pathways in sleep-wake regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of these populations was characterized by differential equations describing the population firing rates which defined the state of the network (see Methods). These equations have been proved to be components of suitable sleep/wake regulatory computational models in previous studies [22, 23, 26, 27, 35]. The pathways from one population to the other were either excitatory or inhibitory.…”
Section: Resultsmentioning
confidence: 97%